Comprehensive analysis of the microbial consortium in the culture of flagellate Monocercomonoides exilis - Alejandro Jiménez-González; Sebastian Cristian Treitli; Priscila Peña-Diaz; Anna Janovská; Vladimír Beneš; Petr Žáček; Vladimír Hampl (Environmental Microbiome)
Abstract Monocercomonoides exilis is a model species of the amitochondrial eukaryotic group Oxymonadida, which makes it a suitable organism for studying the consequences of mitochondrial loss. Although M. exilis has an endobiotic lifestyle, it can be cultured in vitro in polyxenic conditions alongside an uncharacterized prokaryotic community, while attempts to create axenic cultures have not been successful. In this study, we used metagenomic sequencing, transcriptomics, and metabolomics to characterize the microbial consortium that supports the growth of M. exilis. We assembled genomes for 24 bacterial species and identified at least 30 species in total. M. exilis accounted for less than 1.5% of the DNA reads, while bacterial species dominated the sequence data and shifted in abundance over time. Our metabolic reconstruction and differential gene expression analyses show that the bacterial community relies on organic carbon oxidation, fermentation, and hydrogen production, but does not engage in methanogenesis. We observed rapid depletion of amino acids, nucleotides, glyceraldehyde, lactate, fatty acids, and alcohols in the medium, indicating a reliance on external nutrient recycling. The nitrogen cycle in this community is incomplete, with limited nitrogen fixation and no ammonia oxidation. Despite detailed metabolic profiling, we did not find any direct biochemical connections between M. exilis and the prokaryotes. Several bacterial species produce siderophores to assist themselves and others in the community in acquiring iron. However, M. exilis does not appear to benefit directly from siderophore-mediated iron transport and lacks known iron uptake pathways. This indicates that M. exilis may rely indirectly on the iron metabolism of other bacteria through phagocytosis. Additionally, some bacteria synthesize polyamines like spermidine and phosphatidylcholine, which M. exilis may need but cannot produce on its own. As the culture ages, M. exilis shows changes in gene expression consistent with starvation responses, including the upregulation of carbohydrate storage pathways and processes related to exocytosis. These findings provide new insights into microbial interactions within xenic cultures and emphasize the complex nature of maintaining amitochondriate eukaryotes in vitro.